Friendship segregation and class composition in schools: A systematic analysis of the role of attribute consolidation - Böller, Susanne; Kruse, Hanno (PLOS ONE, 2026)
In schools around the world students are sorted to different groups, courses, or classes. In increasingly diverse societies, such sorting practices play an important role to social cohesion. They set the structural conditions for students to form friendships across demographic divides. This article highlights the importance of attribute consolidation in learning contexts, the extent to which demographic categories align or cross-cut each other, a compositional feature largely overlooked in practical school settings. In Study 1, a comprehensive analysis of the association of attribute consolidation and friendship segregation in 524 school classes in Germany, the Netherlands, and Sweden reveals the outstanding significance of gender consolidation. This means that friendships are far more segregated along an attribute when it aligns with gender in a classroom than when it coincides with other attributes, such as socio-economic status or place of residence. Based on this finding, Study 2 uses simulations to examine the potential effects of class-placement strategies that reduce gender consolidation. The results suggest that, relative to observed class placement in Germany, the Netherlands, and Sweden, class placement that minimizes gender consolidation can decrease friendship segregation in that it reduces students’ share of ingroup friends by 4–7 percentage points. More generally, the potential impact of paying attention to gender consolidation in class placement is the largest in diverse schools, which are mostly located in diverse countries with low levels of between-school segregation.